Pengaruh Kepemilikan Negara Dan Kepemilikan Publik Terhadap Kinerja Keuangan BUMN - Chermian Eforis (Ultima Accounting : Jurnal Ilmu Akuntansi, 2017)
Law on State Owned Enterprises (No.19/2003) define one of the purpose of privatization to increase the firm performance and firm value. However, until June 2017, from 119 State Owned Enterprises (BUMN) in Indonesia, only 19 firms have go public. The aim of the research is to examine the effect of state ownership and public ownership towards firm performance proxied based on Return on Equity (ROE) partially and simultaneously. Multiple regression analysis is performed on the data which are collected by using purposive sampling technique for the Indonesia’s State Owned Enterprise (BUMN) listed in the Indonesia Stock Exchange during 2012-2015. We find that state ownership has no effect towards ROE. However, public ownership proxied based on percentage of public ownership has significant effect towards ROE. Keywords: BUMN, Public Ownership, ROE, State Ownership